Beneficial Effects of Ocimum gratissimum Aqueous Extract on Rats with CCl4-Induced Acute Liver Injury. (27th June 2012) - Chiu, Chun-Ching; Huang, Chih-Yang; Chen, Tzy-Yen; Kao, Shao-Hsuan; Liu, Jer-Yuh; Wang, Yi-Wen; Tzang, Bor-Show; Hsu, Tsai-Ching
Abstract : Ocimum gratissimum (OG) is known as a food spice and traditional herb, which has been recommended for the treatment of various diseases. To investigate the hepatoprotective effect of OG aqueous extract (OGAE), male Wistar rats challenged by carbon tetrachloride (CCl4 ) were used as the animal model of chronic hepatic injury. Significantly increased serum catalase and DPPH levels were detected in CCl4 -administrated rats that were treated with OGAE or silymarin as compared to those rats that were treated with saline or CCl4 . In contrast, significantly decreased stress proteins including HSP70 and iNOS were observed in livers of CCl4 -administrated rats that were treated with OGAE or sylimarin as compared to those rats that were treated with saline or CCl4 . Moreover, significant decreases of MMP-9/MMP-2 ratio, uPA, phosphorylated ERK (p-ERK) and NF- κ B (p-P65) were detected in livers of CCl4 -administrated rats that were treated with OGAE or sylimarin as compared to those rats that were treated with saline or CCl4 . These findings imply that OGAE can efficiently inhibit CCl4 -induced liver injuries in rats and may therefore be a potential food or herb for preventing liver injuries.